DISCOURSES, A COMMUNITY OF SCIENTISTS, AND LONG-TAIL DATA IN THE CLOUD - Brooks, Catherine; Heidorn, P. Bryan; Stahlman, Gretchen; Chong, Steven (AoIR Selected Papers of Internet Research, 2015)
Data sharing and related infrastructure dilemmas are of interest across a wide variety of scientists, salient for those engaging with ‘little’ or big data. Scientists tend to work with technologist and engineers as part of their working teams (smaller projects often rely on graduate students working in laboratories). So, it is easy to imagine the ways in which shifts in scholarly practice, data collection, and the management of information – especially in an age of big data – are of paramount importance across sectors and to those coming from the entire research spectrum. To interrogate contemporary concerns in science about data management, particularly that in the cloud, the following research question was posed: RQ: How do issues with sharing data in the cloud get discursively situated by an interdisciplinary group of scientists?